Presentation of the monograph Introduction to Korean language and Korean linguistics - Nećak Lük, Albina (Acta linguistica asiatica, 2024)
Introduction to the Korean Language and Korean Linguistics goes beyond the usual grammatical approaches to presenting the structures of a language. The presentation of the Korean language does not rely only on traditional Korean grammar but also reflects and applies the latest findings of linguistic research in interpreting Korean linguistic phenomena. In addition to an insight into the title theme, it gives a glimpse into general linguistic and sociolinguistic phenomena. It is particularly valued by its theoretical and comparative approach, which helps the reader to gain a deeper understanding of linguistic phenomena in the Korean language and to deal with similar phenomena in their own and other languages. (an excerpt from the review)
Keywords: korejski jezik; korejsko jezikoslovje; korejščina; ocene in poročila; Uvod v korejski jezik in korejsko jezikoslovje; Vzhodna Azija